Life history traits and breeding success of the scarlet-headed blackbird (Amblyramphus holosericeus) in the Argentinean Pampas - Fernández, G.J. (2007)
In this paper we present data on the nesting success and life history traits of the Scarlet-headed Blackbird (Amblyramphus holosericeus) nesting in the Argentinean pampas. During the 1995-1997 and 2001-2002 breeding seasons (September-December), we found 60 Scarlet-headed Blackbird nests. About 40% of these nests produced fledglings, and daily nest mortality did not differ among nesting stages (laying, incubation, nestling). Clutch size was 3 eggs, and the mean number of fledglings was 1.33 ± 0.78. Brood reduction was a common cause of nestling loss as 39% of nest with more than 1 nestling lost the last hatched one. Results obtained from experimental nests indicate that parent nest attention increases the probability of nest success as natural nests showed a lower predation rate. We suggest that the high nest attention detected in this species could be responsible for the higher nesting success compared to other sympatric marsh nesting species. However, high nest attendance could also imply an additional cost as it may constrain the time available to parents for foraging, thus limiting the food delivered to nestlings. © The Neotropical Ornithological Society.